DESCRIPTION OF THE USE OF EYE PROTECTION EQUIPMENT AND THE DIRECT EFFECT OF USE OF WELDING ON THE EYES OF WELDER WORKERS - Saputri, Novricia Agnes (Jurnal MedScientiae, 2024)
A welder is anyone, amateur or professional, who uses welding equipment. A metalsmith who specialize input the ingredients together and usually metal. In carrying out their work, workers will be constantly exposed to high-intensity welding light. Welding workers who do not use proper eye protection can experience direct effects from welding. This literature review is a literature review that uses the method of searching articles in databases, such as PubMed, Google Scholar and manual searches which are then analyzed as many as 10 of the 137 journals obtained. The results showed that the most common use of eye protection was welding goggles with the highest prevalence of eye protection in welding workers, namely 98.4%. The prevalence of complaints in the eyes of welders with the largest prevalence is 74.5%. Welders experience eye complaints in the form of watery eyes, red eyes, eye strain, corneal injuries, and conjunctival disorders and presbyopia. The immediate effect that often occurs is in the form of complaints of watery eyes and then experiencing red eyes.